Effect of Intensive vs Standard Blood Pressure Treatment Upon Erectile Function in Hypertensive Men: Findings From the Systolic Blood Pressure Intervention Trial. (19th December 2019) - Foy, Capri G.; Newman, Jill C.; Russell, Greg B.; Berlowitz, Dan R.; Bates, Jeffrey T.; Burgner, Anna M.; Carson, Thaddeus Y.; Chertow, Glenn M.; Doumas, Michael N.; Hughes, Robin Y.; Kostis, John B.; Buren, Peter van; et al.
Abstract: Introduction: The effect of intensive blood pressure control upon erectile function in men with hypertension, but without diabetes, is largely unknown. Aim: To examine the effects of intensive systolic blood pressure (SBP) lowering on erectile function in a multiethnic clinical trial of men with hypertension. Methods: We performed subgroup analyses from the Systolic Blood Pressure Intervention Trial ([SPRINT]; ClinicalTrials.gov : NCT120602, in a sample of 1255 men aged 50 years or older with hypertension and increased cardiovascular disease risk. Participants were randomly assigned to an intensive treatment group (SBP goal of <120 mmHg) or a standard treatment group (SBP goal of <140 mmHg). Main Outcome Measure: The main outcome measure was change in erectile function from baseline, using the 5-item International Index of Erectile Function (IIEF-5) total score, and erectile dysfunction ([ED]; defined as IIEF-5 score ≤21) after a median follow-up of 3 years. Results: At baseline, roughly two-thirds (66.1%) of the sample had self-reported ED. At 48 months after randomization, we determined that the effects of more intensive blood pressure lowering were significantly moderated by race-ethnicity (p for interaction = 0.0016), prompting separate analyses stratified by race-ethnicity. In non-Hispanic whites, participants in the intensive treatment group reported slightly, but significantly better change in the IIEF-5 score than those in the standard treatment group (mean difference = 0.67; 95% CI = 0.03, 1.32; P = 0.041). In non-Hispanic blacks, participants in the intensive group reported slightly worse change in the IIEF-5 score than those in the standard group (mean difference = −1.17; 95% CI = −1.92, −0.41; P = 0.0025). However, in non-Hispanic whites and non-Hispanic blacks, further adjustment for the baseline IIEF-5 score resulted in nonsignificant differences ( P > 0.05) according to the treatment group. In Hispanic/other participants, there were no significant differences in change in the IIEF-5 score between the two treatment groups ( P = 0.40). In a subgroup of 280 participants who did not report ED at baseline, the incidence of ED did not differ in the two treatment groups ( P = 0.53) and was without interaction by race-ethnicity. Clinical Implications: The effect of intensive treatment of blood pressure on erectile function was very small overall and likely not of great clinical magnitude. Strength & Limitations: Although this study included a validated measure of erectile function, testosterone, other androgen, and estrogen levels were not assessed. Conclusion: In a sample of male patients at high risk for cardiovascular events but without diabetes, targeting a SBP of less than 120 mm Hg, as compared with less than 140 mm Hg, resulted in statistically significant effects on erectile function that differed in accordance with race-ethnicity, although the clinical importance of the differences may be of small magnitude.